Efficient arc sources of gas-discharge plasma in vacuum-plasma production facilities - Borisov D. P.; Koval N. N. Nikolay Nikolaevich; Korotaev A. D.; Kuznetsov V. M.; Romanov V. Ya.; Silchenko P. N.; Terekhov P. A.; Chulkov E. V. (2012, 2012)
Заглавие с экрана